3D nitrogen-doped carbon frameworks with hierarchical pores and graphitic carbon channels for high-performance hybrid energy storages - Choi, Jae Won; Park, Dong Gyu; Kim, Keon-Han; Choi, Won Ho; Park, Min Gyu; Kang, Jeung Ku (Royal Society of Chemistry, 2024)
In principle, hybrid energy storages can utilize the advantages of capacitor-type cathodes and battery-type anodes, but their cathode and anode materials still cannot realize a high energy density, fast rechargeable capability, and long-cycle stability. Herein, we report a strategy to synthesize cathode and anode materials as a solution to overcome this challenge. Firstly, 3D nitrogen-doped hierarchical porous graphitic carbon (NHPGC) frameworks were synthesized as cathode materials using Co-Zn mixed metal-organic frameworks (MOFs). A high capacity is achieved due to the abundant nitrogen and micropores produced by the MOF nanocages and evaporation of Zn. Also, fast ion/electron transport channels were derived through the Co-catalyzed hierarchical porosity control and graphitization. Moreover, tin oxide precursors were introduced in NHPGC to form the SnO2@NHPGC anode. Operando X-ray diffraction revealed that the rescaled subnanoparticles as anodic units facilitated the high capacity during ion insertion-induced rescaling. Besides, the Sn-N bonds endowed the anode with a cycling stability. Furthermore, the NHPGC cathode and SnO2@NHPGC achieved an ultrahigh energy density (up to 244.5 W h kg-1 for Li and 146.1 W h kg-1 for Na), fast rechargeable capability (up to 93C-rate for Li and 147C-rate for Na) as exhibited by photovoltaic recharge within a minute and a long-cycle stability with similar to 100% coulombic efficiency over 10 000 cycles. 3D nitrogen-doped hierarchical porous graphitic carbon cathode and subnanometric tin oxide nanocrystals anode materials are derived from Co-Zn mixed metal-organic frameworks to achieve high-performance Li-ion and Na-ion hybrid energy storage devices.